2012
DOI: 10.4236/ojanes.2012.24034
|View full text |Cite
|
Sign up to set email alerts
|

Can Simple Preoperative Hemoglobin Testing Screen Symptomatic Anemia in Patients Undergoing Ambulatory Surgeries in Third World Countries?

Abstract: Background: Patients coming for ambulatory surgeries are mostly healthy adults and asymptomatic anemia in these patients is rare. According to international standards, perioperative period is not an appropriate setting to screen and investigate the cause of asymptomatic anemia, but in third world countries where iron deficiency is rampant, it is generally required as per local hospitals policy to test hemoglobin levels prior to any surgery in order to prevent morbidity. The purpose of our study is to look at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…In patients with abnormal test results peri-operative intervention was required in only 35 (0.43%) cases. Amongst abnormal test results low haemoglobin level was the most common abnormality (15.49%), as also reported from other developing countries 8 , while most studies from Western world found anaemia in less than 3% of patients 9 . Generally, low haemoglobin contributes little to patient’s surgical management or morbidity 10 and most cases of anaemia which are significant enough for patient’s management can be detected clinically 11 .…”
Section: Discussionsupporting
confidence: 74%
“…In patients with abnormal test results peri-operative intervention was required in only 35 (0.43%) cases. Amongst abnormal test results low haemoglobin level was the most common abnormality (15.49%), as also reported from other developing countries 8 , while most studies from Western world found anaemia in less than 3% of patients 9 . Generally, low haemoglobin contributes little to patient’s surgical management or morbidity 10 and most cases of anaemia which are significant enough for patient’s management can be detected clinically 11 .…”
Section: Discussionsupporting
confidence: 74%
“…This is similar to the finding in this study where nine females and two males had their hematocrit less than 30% with a prevalence of 2.6%. Other researchers used the WHO definition of anemia to determine their hemoglobin cut-off level with varying prevalence of anemia ranging from 12 % in general surgical patients to 35% in patients undergoing orthopedic surgery [11][12][13]. These authors reported that more females where anemic than the males.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review regarding complete blood count (CBC) revealed that some of the available studies had tested individual components of CBC, that is, haemoglobin or haematocrit, total and differential leukocyte count and platelet count, while others had tested CBC as a whole. [ 3 11 12 13 19 20 21 22 23 24 ]…”
Section: Guidelines and Recommendationsmentioning
confidence: 99%
“…Anaemia is a global health issue with a prevalence rate of approximately 14% in ASA PS 1 and 2 preoperative patients. [ 3 11 12 13 19 20 21 22 23 24 25 26 27 ] This can contribute to adverse events such as tachycardia, arrhythmias, increased risk of infection, heart failure in the perioperative period. It can also contribute to increased duration of hospital stay, rates of intensive care admission and blood transfusion, which carry their own associated risks.…”
Section: Guidelines and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation